(untitled) - Cunningham, William P. (Boston, 2010)
"Environmental Science: A Global Concern, Eleventh Edition", is a comprehensive presentation of environmental science for non-science majors which emphasises critical thinking, environmental responsibility, and global awareness. This book is intended for use in a one- or two-semester course in environmental science, human ecology, or environmental studies at the college or advanced placement high school level.
Keywords: Environmental sciences,Khoa học môi trường